Fractured carbonates in the Mediumfjellet thrust-stack in the Tertiary fold-and-thrust belt of Spitsbergen - Larsen, Tine (Universitetet i Tromsø, 2009)
This thesis describes a study that was carried out in the Tertiary fold-and-thrust belt of Svalbard, in the mountain range of Mediumfjellet summer 2007 and 2008. The focuses were on: i) further describing the larger structures of the Mediumfjellet, ii) analyze the fracture distribution in the limestone beds associated with the major structures in the area. Available data sets are based on photo textured Lidar scan and extensive field observations. The Mediumfjellet thrust stack is situated in the so-called central zone of the Spitsbergen fault-and-thrust belt. The mountain range displays three in-sequence thrusts (M1, M2, and M3) and one out-of-sequence thrust (G), with associated hanging wall anticlines. The anticlines are in general upright and tight, locally with overturned forelimbs, and characterized by thickening of the hinge zone and thinning of the forelimb. Lateral variations caused by oblique ramps, fault segment linkage, and lateral changes in the fold geometry and the fold plunge make the thrust system a complex deformation zone. The fracture system has been divided into three populations, namely; i) Perpendicular fractures including conjugate shear fractures and extensional fractures, ii) conjugate hybrid shear fractures, and iii) thrust fractures. Based on the systematic relationships to the fold axis, the perpendicular and hybrid fractures, are interpreted as syn-folding fractures, whereas observations of folded thrust fractures support a pre-folding event. This study thereby suggests a 2 stage kinematic fracture model, where the pre-folding thrust fractures indicate a NW-SE to N-S contraction, and the syn-folding fractures reveal NW-SW to E-W contraction. Fractures that do not fit into this model are assumed to be a result of lateral local variations or reactivation of existing fractures. When comparing the fracture intensity to the fold domains, the highest intensity is situated in the hinge zone. This implies a fold mechanism with fixed hinge folding, most commonly ascribed to fault-propagation ...